1994
DOI: 10.1159/000176466
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Effects of the Diuretic Torasemide

Abstract: Torasemide is a lipophilic loop diuretic which is largely metabolized in the liver and has an almost neutral pKa. Experiments were designed to address the questions of whether torasemide is secreted by the proximal tubule, and hence accumulates in tubular fluid, whether torasemide paralyses active transport in the cortical thick ascending limb of the nephron and hence reduces its ATP requirement, and finally whether torasemide is active in its protonated or unprotonated form. Intravenous torasemide, 10 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…We confirmed that torsemide interacts with the human OATs 1, 3 and 4 in vitro as was expected from an earlier clinical study and in vitro studies with other loop diuretics [11,12]. We observed a 6.6-fold interindividual variation in the renal clearance of torsemide, compared with about a twofold difference in creatinine clearance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We confirmed that torsemide interacts with the human OATs 1, 3 and 4 in vitro as was expected from an earlier clinical study and in vitro studies with other loop diuretics [11,12]. We observed a 6.6-fold interindividual variation in the renal clearance of torsemide, compared with about a twofold difference in creatinine clearance.…”
Section: Discussionsupporting
confidence: 90%
“…Torsemide is a loop diuretic that is eliminated renally with a clearance of the unbound fraction (1–2%) of about 1200 ml min −1 [8]. Thus, torsemide is thought to be eliminated primarily via active anion secretion, and that its active excretion accounts for about 90% of torsemide renal clearance [8, 12]. However, the interaction of torsemide with the OATs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Its mode of action, pharmacokinetics, and pharmacodynamics have been reported in a variety of clinical situations [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%